(untitled) (MAUSAM, 1982)
The present paper deals with the study of elevated radio ducts over seas along the east and west coasts of India in association with trade wind inversion during the months June through September. This study was specially undertaken after a few reports of abnormal super-refraction and ducting phenomena near the Bombay coast during June-September 1974 when signals of Karachi T. V. station could be received by T. V. sets around Bombay and Pune. Morning (OD GMT) and evening (12 GMT) radiosonde data from surface to 500 mb (5.8 km) for the three coastal stations, viz., Calcutta and Visakhapatnam on the east coast and Bombay on the west coast during June to September 1974 were utilised in the present study. Vertical profiles of radio refractivity (N) over these stations during this period were worked out, plotted and layers of elevated radio ducts were Identified, tabulated and radio propagation conditions over the east and west coasts of India were discussed in the paper.